Antibacterial Effect of Allium ampeloprasum and Allium porrum Extracts on Staphylococcus aureus and Pseudomonas aeruginosa - Shahin Gavanji; Azizollah Bakhtari; Hojjat Baghshahi; Zahra Hamami Chamgordani; Akram Sadeghi (Korean Pharmacopuncture Institute, 2023)
Objectives: The most prominent microorganisms that cause hospital infections and acquire antibiotic resistance are Staphylococcus aureus and Pseudomonas aeruginosa. The present study aimed to compare the phenolic and flavonoid compounds of various Allium ampeloprasum and Allium porrum extracts and evaluate the antibacterial effects of these extracts against these two microorganisms.Methods : : The total phenolic and flavonoid contents of the acetone, methanol, aqueous, and hexane leeks extracts from A. ampeloprasum and A. porrum were measured. The antibacterial activity of these extracts against S. aureus and P. aeruginosa was tested using the disk diffusion method for 24, 48, and 72 hours. Further, the minimum inhibitory concentrations and the minimum bactericidal concentrations of these extracts for these two bacteria were evaluated and compared with those of common antibiotics.Results : : The aqueous extracts showed the highest phenolic and flavonoid contents and at concentrations of 35 and 40 mg per disk, showed the most antibacterial activity against S. aureus and P. aeruginosa; P. aeruginosa showed more sensitivity to the aqueous extracts than S. aureus.Conclusion : : Aqueous A. ampeloprasum and A. porrum extracts may prevent the growth of hospital pathogens, especially P. aeruginosa; our findings will aid the discovery of new antimicrobial substances against antibiotic-resistant bacteria.